Peningkatan Hasil Belajar Peserta Didik Menggunakan Model Problem Based Learning (PBL) Berbantuan Media Berbasis Canva Pada Mata Pelajaran Pendidikan Pancasila di Kelas V SDN 01 Asam Kumbang Kabupaten Pesisir Selatan - Husna, Fidrathul; Iraqi, Hana Shilfia; Putera, Rafhi Febryan; Zuryanty, Zuryanty (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to describe how to improve student learning outcomes in Pancasila Education learning using the Problem Based Learning (PBL) model in class V SDN 01 Asam Kumbang Kabupaten Pesisir Selatan. This research is a Classroom Action Research (CAR) using qualitative and quantitative approaches, which is implemented in two cycles, namely cycle I (two meetings) and cycle II (one meeting) carried out in four stages, namely planning, implementation, observation and reflection. The subjects of this study were teachers and students of class V SDN 01 Asam Kumbang Kabupaten Pesisir Selatan with a total of 19 students, 8 boys and 11 girls. The results of this study showed an increase in the teaching module cycle I with an average of 85.41% (Good) and cycle II 95.83 (Very Good). Assessment of teacher activity cycle I with an average of 82.14% (Good) and cycle II 96.42% (Very Good). Assessment of student activity cycle I with an average of 82.14% (Good) and cycle II 96.42% (Very Good). Assessment of students in improving learning outcomes in cycle I obtained 74.94% and cycle II with an average of 85.76%. Based on these results, it can be concluded that the Problem Based Learning (PBL) model can improve learning outcomes of Pancasila Education in grade V.